Síntese, caracterização, cálculos de DFT e atvidade antifúngica de novos derivados da piperina - Souza Junior, Joselito da Silva (2021)
This work describes the synthesis of four new piperine derivatives (PC1-PC4), which were obtained through the bimolecular nucleophilic substitution reaction (SN2) between bromoacetophenones and potassium piperate with yields ranging between 58% and 65%. The compounds were characterized by infrared spectroscopy (IR), NMR of 1H and 13C. For the compounds, quantum calculations were made using the density functional theory (DFT) on the basis of B3LYP-D3/6-31G(d,p) and 6-311+G(2d,p) and with this the electronic properties of each molecule to verify the energy gap between the HOMO and LUMO orbitals and some global chemical reactivity descriptors such as Electrophilicity, Chemical Potential and Hardness, which were used to study the reactivity and stability of the aforementioned compounds. The 1H and 13C chemical shifts were calculated using the gauge-invariant atomic orbital method (GIAO) and compared with the experimental values. In addition, the calculations of coefficient of determination (R2 ) for the chemical shift of 13C ranged between 0.96 and 0.99 and for 1H ranged between 0.90 and 0.97, R2 was performed to determine which synthesized compound had the best correlation between experimental and calculated chemical shifts, and PC3 was the substance with the best coefficient of determination was PC3. The compounds were evaluated in an antifungal study against strains of Candida albicans ATCC 76645, C. albicans LM-111, C. albicans LM-122, C. tropicalis ATCC-13803, C. tropicalis LM-04, C. krusei LM-656 , C. krusei LM-13, Trichophyton rubrum LM-49, Microsporum canis LM-12, M. gypseum LM-512. Aspergillus flavus LM-171, LM-248, Aspergillus niger LM-22, Penicillium citrinum LM-278, LM-161, Cladosporium sp LM-283. After the antifungal study, the PC4 compound showed 81.25% inhibition in sixteen strains tested with a minimum inhibitory concentration (MIC) value ranging from 1.23-2.46 μmol mL-1 and the minimum fungicidal concentration (MFC) varied between 9.84-19.68 μmol mL-1 showing a fungistatic effect.